Bonamia infection in native oysters (Ostrea edulis) in relation to European restoration projects. Issue 11 (12th November 2020) - Sas, Hein; Deden, Brenda; Kamermans, Pauline; zu Ermgassen, Philine S.E.; Pogoda, Bernadette; Preston, Joanne; Helmer, Luke; Holbrook, Zoë; Arzul, Isabelle; van der Have, Tom; Villalba, Antonio; Colsoul, Bérenger; et al.
Abstract: There is a growing effort throughout Europe to restore populations of native oysters ( Ostrea edulis ), with the ecological objective of enhancing ecosystem biodiversity and resilience. The introduced parasite, Bonamia ostreae, caused catastrophic mortalities during the 1980s, furthering the decline of this species, and is now present throughout much of the natural range of O. edulis . It is therefore important that restoration attempts avoid further introduction and spread of this parasite, which can cause lethal infections of O. edulis . This article presents a comprehensive overview of the scale and distribution of current infection, transmission pathways, and preventive measure guidelines, focusing on the seas, inlets, and estuaries of north‐west Europe, where most ecological restoration attempts for the native European oyster have occurred so far. This is critical information for restoration project planning in which the risk of Bonamia infection must be taken into account.